Photovoltaic powered DC-DC boost converter based on PID controller for battery charging system. (January 2020) - Irwanto, M; Leow, W Z; Ismail, B; Baharudin, N H; Juliangga, R; Alam, H; Masri, M
Abstract: The input voltage of battery charging system is always above the battery nominal voltage and it should be remained constant. But it depends on the type of input voltage sources. A battery charged directly by photovoltaic (PV) module as the input voltage source can cause the output voltage of PV module or the input voltage of battery charging system can fluctuate, because the output voltage of PV module depends on the solar irradiance. This problem can be solved by installing DC-DC boost converter between the PV module and battery. This paper presents a DC-DC boost converter based on PID controller for battery charging system. It is designed for the input voltage of 12V and output voltage of 14.7V system because it is applied to charge a 12 V, 7 Ah lead acid battery. Based on the simulation result of battery charging system shows that the output voltage of DC-DC boost converter can be remain around 14.7 V. It is due to the PID controller can damp the voltage oscillation and remain its steady state voltage. The time needed by the DC-DC boost converter to charge the battery in the fully charging condition is 1 hour: 3 minutes: 37seconds.